Effect of salinities on nitrogen removal performance of DHS-USB system and growth of Epinephelus bruneus in closed recirculating aquaculture system. (October 2021) - Kotcharoen, Wilasinee; Watari, Takahiro; Adlin, Nur; Nakamura, Yoshinobu; Satanwat, Penpicha; Pungrasmi, Wiboonluk; Powtongsook, Sorawit; Takeuchi, Yutaka; Hatamoto, Masashi; Yamazaki, Shinichi; Yamaguchi, Takashi
Abstract: The aim of this study was to evaluate the effect of salinities on the nitrogen removal performance of a pilot-scale down-flow hanging sponge (DHS) reactor and an up-flow sludge blanket (USB) reactor which was installed in a closed recirculating aquaculture system for the purpose to maintain the water quality in the aquaculture tank. In this study, water quality and the growth of the Longtooth grouper, Epinephelus bruneus, were investigated at 30‰, 22.5‰, and 15‰ salinity for over 1000 days. The tested DHS reactor has successfully maintained total ammonium nitrogen in aquaculture tank at less than 1.0 mg-N·L −1 at various salinities. The abundance of nitrifying bacteria detected in the DHS reactor was higher at salinities of 15‰ and 22.5‰ than at 30‰. The USB reactors achieved a nitrate removal efficiency of over 60%. All fish survived all salinity conditions, exhibiting the highest daily weight gain of 2.0 ± 3.4 g-fish·day −1 at 15‰ salinity, which was 1.6 times higher than that at 30‰. The DHS-USB system could exert nitrogen removal under changing salinity conditions. Highlights: DHS-USB system applied in recirculating aquaculture system with salinity gradient. Salinity changes from 30 to 15 Practical Salinity Unit affects microbial community. Removal of total ammonia nitrogen by DHS-USB system wasn't affected by salinity level. The effect of salinity on growth of Epinephelus bruneus were investigated.